Persepsi Warga Kampus Tentang Rokok, Perilaku Merokok dan Pemberlakuan Kawasan Tanpa Rokok (KTR) di Lingkungan Pendidikan - Sugiyatmi, Tri Astuti; Handoko, Lukman; Wartiningsih, Minarni; Noviani, Doris (Akademi Kebidanan Bunga Husada Samarinda, 2024)
Cigarettes and smoking behavior are public health problems. Together with other bad lifestyles such as lack of movement, stress, lack of balanced nutrition, and alcohol consumption, smoking is a risk factor for non-infectiou diseases. The bad effects of cigarettes are clear, but cigarettes and smoking behavior have long been perceived as normal by many people. The research aims to determine the perceptions of campus residents regarding smoking, smoking behavior and the implementation of non-smoking area in the educational environment. This study is an observational survey research. This research involved University of Borneo Tarakan residents, including lecturers, education staff, and students. The respondents obtained were 153 respondents (128 women and 25 men) from 7 faculties selected using a simple sampling technique. The instrument using a perception questionnaire developed by researchers which has been tested for validity and reliability. This research was conducted from June to November 2022. Of all respondents, the number of active smokers was 6 people (3.9%) and 1/3 were women. More than half of the respondents were passive smokers (54.2%). The perception of University of Bornoe Tarakan residents towards cigarettes, smoking behavior and the implementation of non-smoking area seems to vary, leading to good understanding, although there are also those who are in neutral territory regarding the implementation of tobacco/smoking control. Of all respondents, only 1 respondent disagreed with the implementation of non smoking area in education, health and places of worship. From these results it can be concluded that campus residents have a positive perception of the implementation of non-smoking areas in the educational environment.